Family Knowledge About the Management of Acute Respiratory Infection (ARI) in Toddlers in the Children's Clinic of the Madani Hospital - Singkali, Dina Palayukan; Abdullah, Asmiwarti; Supirno (Journal of Health and Nutrition Research, 2023)
This study aims to determine the level of family knowledge about the management of Acute Respiratory Infection (ARI) in toddlers at the Madani Hospital Polyclinic, Central Sulawesi Province. This type of research is descriptive. The variable in this study was family knowledge about the management of ARI in toddlers. The types of data in this study are primary data and secondary data. The analysis used in this research is univariate analysis. The population in this study were families who brought toddlers with ARI to seek treatment at the Children's Polyclinic at Madani General Hospital in Central Sulawesi Province at the time the study was conducted. The sample is 43 people with accidental sampling technique. The results showed that of the 43 respondents, 55.8% had good knowledge, 39.5% had sufficient knowledge and 4.7% lacked knowledge. Most of the family's knowledge about the management of ARI in toddlers is good. Suggestions are expected for health workers at the Madani Public Hospital Children's Polyclinic to be more proactive in taking preventive measures related to ARI in toddlers, so that the morbidity and mortality due to ARI will decrease.